2019
DOI: 10.1002/oby.22574
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rate Bias in Participants with Severe Obesity Regardless of Deindexation

Abstract: Objective Morbid obesity is associated with a higher independent risk of chronic kidney disease (CKD). Estimated glomerular filtration rate (eGFR) has been evaluated in a limited number of study participants with severe obesity. Methods A total of 706 measured GFR (mGFR) results from 598 participants with obesity (BMI ≥ 35 kg/m2) were retrospectively collected. The performance of the Modification of Diet in Renal Disease (MDRD) equation, Chronic Kidney Disease‐Epidemiology (CKD‐EPI) equation, and deindexed eGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The authors concluded that the BSA‐indexed eGFR, regardless of the use of CKD‐EPI or MDRD equations, tends to overestimate kidney function in morbid obesity. Deindexation did not remedy the biases and inaccuracies of eGFR and indeed worsened the overestimation according to the authors .…”
Section: Comparing Serum Cystatin C and Creatinine As Kidney Filtratimentioning
confidence: 75%
See 2 more Smart Citations
“…The authors concluded that the BSA‐indexed eGFR, regardless of the use of CKD‐EPI or MDRD equations, tends to overestimate kidney function in morbid obesity. Deindexation did not remedy the biases and inaccuracies of eGFR and indeed worsened the overestimation according to the authors .…”
Section: Comparing Serum Cystatin C and Creatinine As Kidney Filtratimentioning
confidence: 75%
“…Similarly, fasting for Ramadhan increased the eGFR likely because of loss of muscle and/or reduction of dietary meat intake . Notwithstanding these data, it is not clear why the eGFR overestimated the mGFR in morbid obesity in the study by Guebre‐Egziabher et al . However, the removal of indexation for BSA did not improve the estimate but worsened it.…”
Section: Comparing Serum Cystatin C and Creatinine As Kidney Filtratimentioning
confidence: 84%
See 1 more Smart Citation
“…The second large study was a retrospective evaluation comparing the performance of MDRD4 and CKD-EPI equations with inulin or iohexol in 598 patients with various nephropathies and BMIs ≥35 kg/m 2 (mean 39.6 ± 4.3 kg/ m 2 ). 36 [47 to 54] mL/min/1.73 m 2 , respectively; P < 0.01 for both), with deindexing increasing the overestimation (data not shown). These 2 studies evaluating the performance of MDRD4 and CKD-EPI in patients with obesity indicate significant biases and inaccuracies compared with mGFR.…”
Section: Mdrd and Chronic Kidney Disease Epidemiology Collaborationmentioning
confidence: 93%
“…The second large study was a retrospective evaluation comparing the performance of MDRD4 and CKD-EPI equations with inulin or iohexol in 598 patients with various nephropathies and BMIs ≥35 kg/m 2 (mean 39.6 ± 4.3 kg/m 2 ). 36 The median absolute bias (99.6% CI) was significantly greater for MDRD4 compared with CKD-EPI (8.0 [6.8-9.6] vs 7.3 [6.4-8.6], respectively; P < 0.05) and accuracy defined as within 30% of mGFR was significantly less with MDRD4 (75 [69-79] vs 78 [73-83], respectively; P < 0.05). However, both the MDRD4 and CKD-EPI equations significantly overestimated mGFR (median [95% CI], 55 [53-59] mL/min/1.73 m 2 and 56 [53-58] mL/min/1.73 m 2 vs 50 [47 to 54] mL/min/1.73 m 2 , respectively; P < 0.01 for both), with deindexing increasing the overestimation (data not shown).…”
Section: Estimate Of Glomerular Filtration Ratementioning
confidence: 99%